Analysis of BRIsat Investment Success from Financial and Nonfinancial Perspectives - Adyasari, I Gusti Ayu Agung Wiwin; Dwi Putri, I Gst. Agung Pramesti; Dewi, Eka Grana Aristyana (Politeknik Negeri Batam, 2026)
Investment in information technology within the banking sector requires not only financial viability but also public acceptance, particularly for state-owned enterprises (SOEs) that carry both commercial and social mandates. This study aims to evaluate the success of PT Bank Rakyat Indonesia (Persero) Tbk.’s BRIsat satellite investment from both financial and nonfinancial perspectives. A Cost–Benefit Analysis (CBA) was employed to assess financial feasibility using BRI’s publicly available financial statements from 2014 to 2024, while sentiment analysis using the Naive Bayes algorithm was conducted to examine public perception based on social media data from platform X covering the period 2016–2024. The financial analysis indicates that the BRIsat investment is financially feasible, with a Return on Investment (ROI) of 2.58%, a Payback Period of 6.2 years, a positive Net Present Value (NPV) of IDR 166,161,960, and a Benefit Cost Ratio (BCR) of 184.9, suggesting that every IDR 1 invested generates IDR 184.9 in economic benefits. From the nonfinancial perspective, sentiment analysis of 10,066 valid tweets reveals that 55.90% of public sentiment is negative (5,627 tweets), while 44.10% is positive (4,439 tweets), with the Naive Bayes model achieving an accuracy of 96.76%. Positive sentiment is primarily associated with keywords such as “successful,” “fast,” and “service,” reflecting appreciation for BRIsat as a strategic innovation, whereas negative sentiment is dominated by terms such as “error,” “failed,” and “disruption,” indicating persistent technical issues in digital banking services. These findings highlight a clear contradiction between the strong financial performance of the BRIsat investment and the predominantly negative public perception of service quality. The study implies that the success of large-scale technology investments in SOEs cannot be assessed solely through financial metrics, but must be accompanied by continuous improvements in operational reliability and digital service quality to ensure sustainable value creation and public trust.